Answer:
unsolvable because the second equation is just -2.5 times the first equation.
Step-by-step explanation:
2x-6y=12 then 2x=12+6y x=6+3y
-5x+15y=-30
substitute x
-5(6+3y)+15y=-30
-30-15y+15y=-30
y=y
Answer:
23x = -115
Step-by-step explanation:
In the substitution method, you must solve for 1 variable in 1 equation to replace it in the other equation. For the system:
2x - 7y = 4
3x + y = -17
Solving for y in the second equation:
y = -17 - 3x
Replacing y in the first equation:
2x - 7(-17 - 3x) = 4
2x + 119 + 21x = 4
23x = -115
This is the new equation after use the substitution method.
60 because 2:4 is 1/2, and when you divide by a fraction, you multiply by the reciprocal (2/1 instead of 1/2) which would be 60 in this case.
Answer:
Runner-up: $15,000
Winner: $75,000
Step-by-step explanation:
Let's create an equation for this problem.
Let x=the amount the runner-up receives
Let 5x=the amount the winner receives
Then,
x+5x=90,000
6x=90,000
x=15,000
5x=75,000
Answer:
-24
Step-by-step explanation:
Since only one of the factors has a negative sign, the product will be negative.
4 · (-6) = <u>-24</u>